The Future is Now: The Science-Policy Interface for Achieving Sustainable Development - Bonini, Astra (Statistical and Social Inquiry Society of Ireland, 2020)
Strengthening the Science Policy Interface, at all levels of governance, is a key means of implementation the UN 2030 Agenda for Sustainable Development. This short paper addresses our most recent and important reports that works to support Science Policy Interfaces at all levels of governance. This is called the UN Global Sustainable Development Report (UN GSDR) for 2019. The title of the 2019 report is, “The Future Is Now: Science for Achieving Sustainable Development. It focuses on the relevance of science in advancing sustainable development and calls for a drastic change in development policies, incentives and actions informed by research into the interconnectivity of the Sustainable Development Goals (SDGs) if we are to meet the target of achieving the SDGs by 2030. The report acknowledges the role of various actors, such as States, private sector, civil society organisations and the academia in the implementation of the SDGs and points to the urgent need for actors to understand and engage with the scientific realities that underpin the relationship between human activity and the natural world.
read before the Society, 23rd April 2020 - Symposium: Science-Policy Interfaces and the Environment
Keywords: Science Policy Interface; Transformations; Linkages; UN 2030 Agenda; stakeholders; 314.15